Peran Pendidikan Keaksaraan dalam Membangun Kemandirian Ekonomi Masyarakat Desa Bahitom, Kalimantan Tengah - Gabriella, Mardiana (Jurnal Empowerment, 2024)
Literacy education plays a crucial role in enhancing the quality of life, particularly in rural areas that still face challenges in accessing formal education. Literacy is not limited to the ability to read, write, and perform arithmetic but also encompasses the skills to comprehend information and apply it in daily life situations. Bahitom Village, as a rural area, faces numerous challenges in human resource development. Low literacy levels often hinder the community from leveraging economic opportunities and accessing essential information that could enhance their well-being. Literacy education is believed to provide a solid foundation for building economic independence, as literate individuals are better equipped to understand and utilize information for productive activities, such as managing small businesses, agriculture, or other economic ventures. Literacy education programs in rural villages also serve as a means of community empowerment by emphasizing the importance of fundamental skills to enhance participation in socio-economic activities. This study aims to assess the extent to which literacy education contributes to building economic independence in the community of Bahitom Village, Central Kalimantan. It is expected that the findings will offer new insights into the development of community-based literacy programs that are more effective and aligned with local needs. This study was conducted using a qualitative approach and reference-based methods. The choice of these methods was motivated by the focus on research questions closely related to social factors that influence individuals' mindsets, perspectives, attitudes, and behaviors within society. Based on the research findings, literacy education has proven to play a crucial role in fostering the economic independence of the community in Bahitom Village, Central Kalimantan. This program not only enhances basic skills in reading, writing, and arithmetic but also broadens access to information and economic opportunities. With improved literacy, community members are better equipped to manage small businesses, record transactions, and plan economic activities independently.